Targeted mutagenesis of DNA using triple helix-forming oligonucleotides linked to psoralen. - Havre, P A (1993)
Oligonucleotides can bind as third strands of DNA in a sequence-specific manner in the major groove in homopurine/homopyrimidine stretches in duplex DNA. Here we use a 10-base triplex-forming oligonucleotide linked to a psoralen derivative at its 5' end to achieve site-specific, targeted mutagenesis in an intact, double-stranded lambda phage genome. Site-specific triplex formation delivers the psoralen to the targeted site in the lambda DNA, and photoactivation of the psoralen produces adducts and thereby mutations at that site. Mutations in the targeted gene were at least 100-fold more frequent than those in a nontargeted gene, and sequence analysis of mutations in the targeted gene showed that 96% were in the targeted region and 56% were found to be the same T.A to A.T transversion precisely at the targeted base pair. The ability to reproducibly and predictably target mutations to sites in intact duplex DNA by using modified oligonucleotides may prove useful as a technique for gene therapy, as an approach to antiviral therapeutics, and as a tool for genetic engineering.